2021
DOI: 10.3390/fermentation7040223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by Flash GC Electronic Nose of the Effect of Combinations of Yeasts and Nutrients on the Aromatic Profiles of Feteasca Regala Wines after Two Years of Storage

Abstract: Feteasca regala is a semi-aromatic Romanian white grape variety, which can benefit from technological interventions aiming to modulate its aromatic profile. In this study, two specific yeast nutrients, designed to increase the esteric and thiolic aromatic potential, respectively, were added at appropriate times, before or during fermentation. The musts were inoculated with two different strains of yeast, specially selected to favour the formation of an esteric or a thiolic volatile profile. The resulting wines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…and they found out that the grapes had high sugar content at harvest. The wines produced by fermentation with the selected yeasts had more than 15% v/v alcohol concentration, which is unusual for the Feteasca regala variety (Antoce & Cojocaru, 2021). In addition, for the F4A-ET variants in both CS and FR, it was observed that the results for the FR wine are specific for a more balanced wine in terms of acidity and of alcohol concentration in comparison with the CS wine sample obtained with the same yeast biomass.…”
Section: Resultsmentioning
confidence: 86%
“…and they found out that the grapes had high sugar content at harvest. The wines produced by fermentation with the selected yeasts had more than 15% v/v alcohol concentration, which is unusual for the Feteasca regala variety (Antoce & Cojocaru, 2021). In addition, for the F4A-ET variants in both CS and FR, it was observed that the results for the FR wine are specific for a more balanced wine in terms of acidity and of alcohol concentration in comparison with the CS wine sample obtained with the same yeast biomass.…”
Section: Resultsmentioning
confidence: 86%